Flight : a novel - Strong, Lynn Steger, 1983- (Mariner Books, 2022)
"The new novel from the critically acclaimed author of Want, told through the shifting voices of a family gathering for Christmas in upstate New York after the death of their beloved matriarch, at odds over the settling of her estate-a novel about art, grief, shame, ambition, joy, and the American safety net"--